Psychological and Pedagogical Support of Speech Therapy Specialists in the System of Inclusive Education (Journal of Educational Sciences, 2025)
The article considers the role of speech therapists as specialists in the context of inclusive education and issues of their professional support. It highlights the significance of providing psychological and pedagogical assistance to enhance the quality of their practice and explores methods for overcoming challenges inherent in the implementation of inclusive education. The research analyzes the specific requirements and responsibilities of speech therapists in this context, detailing the professional knowledge, competencies, and tools necessary for conducting corrective interventions tailored to children’s diverse physical and psychological characteristics. In addition, the importance of organizing methodological work in educational institutions to improve the professional skills of speech therapists in the context of inclusive education is especially emphasized.The importance of continuous improvement of professional training and methodological knowledge of speech therapists is emphasized. Based on an analysis of survey results, the study organized targeted interventions such as specialized training, seminars, and workshops. These initiatives aimed to increase practitioners' awareness of the inclusive education system and develop their practical skills. The research identifies the primary difficulties that speech therapists encounter when designing effective methods for children with special educational needs and analyzes pathways for improving their professional training and practice within inclusive environments.Key words: inclusive education, speech therapist, children with special educational needs, psychological and pedagogical support, competence.